Knowledge Management Diagnosis in Software Organizations: A Systematic Literature Review Extension - Souza, Wesley; Silva, Williamson; Guedes, Gilleanes Thorwald Araujo (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: Effective Knowledge Management (KM) is vital for tech companies where developers frequently switch, risking the loss of valuable experience. Diagnosing its current state, assessing practices, and understanding applied methodologies in organizations is essential to succeed in KM. Problem: Given the dynamism witnessed in KM, a Systematic Literature Review (SLR) is necessary, and we found an outdated SLR on this topic until 2018. Objective: We extended the SLR to identify the current state-of-the-art KM within organizations and research niches to accurately depict the current management practices. Method: We extended the 2018 SLR, incorporating two additional databases to update this review and allow us to select new studies produced after the original review. IS Theory: This work was conceived under the auspices of the theory of organizational knowledge creation, aiming to understand the influence of KM on the development of information systems (IS) today. Summary of Results: We evidenced 29 studies on KM Diagnosis in software development organizations. Conclusion: Results show significant changes in applying learning to organizational culture through KM. Internal techniques, not tools or literature models, are now prevalent in km development. Agile methodology is a central focus in KM studies. The same holds for software architectures, with minimal application of KM in their selection and development. Contributions and Impact in the IS area: We believe in identifying KM strategies that facilitate the formation of new teams, transmitting knowledge and experiences, developing new products, and maintaining existing ISs.